Asuhan Kebidanan Continuity Of Care (Coc) Ny.E Umur 36 Tahun di Klinik Aria Medistra Kabupaten Semarang Jawa Tengah - Bq. Yulia Sri Aprian (Universitas Ngudi Waluyo, 2023)
Continuity of care in midwifery is a series of continuous and comprehensive service activities starting from pregnancy, childbirth, postpartum, newborns and family planning services that connect the health needs of women in particular and the personal circumstances of each individual. This aims to help monitor and detect possible complications that accompany the mother and baby from pregnancy until the mother uses family planning. Midwives have an important role as implementers, such as midwives providing midwifery care for pregnancy and family planning acceptors, midwives as administrators, such as managing community health activities, especially regarding mothers and children, and midwives as educators, such as midwives providing health education and counseling to clients, training and guiding cadres. The midwifery care method at the Aria Medistra Pringapus Clinic, Semarang Regency, Central Java uses descriptive methods, data collection techniques, namely interviews, observation of providing physical examination care, supporting examinations, documentation studies and bibliography studies. The subject of the case study is Mrs. E, the subject is carried out based on the goals to be achieved. This case study was carried out from May to November 2023. The midwifery care provided to Mrs. , neonates twice, and family planning twice. In Mrs.